The Relevance of Evaluation to Learning Objectives in Instructional Planning - Rahayu, Martini (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Early childhood refers to children aged 0-6 years with unique and distinct traits. According to Suryana, as cited by Syahrul & Nurhafizah (2021: 685), early childhood encompasses children within a specific age range, exhibiting unique characteristics and undergoing rapid and foundational developmental processes crucial for their future lives. Education can be conducted anywhere, and one of the institutions providing education is schools. Educational institutions serve as the venues for the teaching-learning process, delivering formal instruction to enhance the quality of education (Olli Susanti & Pautina Amalia, 2020). Teachers play a crucial role in instructional planning as they design, implement, and assess learning activities. Teachers can create diverse learning activities and engage learners using instructional media to make the learning process more captivating and interactive, necessitating innovation in learner-centered instruction, one of which involves using instructional media.